Rotatory Knee Instability : An Evidence Based Approach - Musahl, Volker; Karlsson, Jón; Kuroda, Ryosuke; Zaffagnini, Stefano (Springer International Publishing : Imprint: Springer, 2017)
This book is designed to equip the reader with the knowledge and tools required for provision of individualized ACL treatment based on the best available evidence. All major aspects of the assessment of rotatory knee instability are addressed in depth. A historical overview of arthrometers, both invasive and non-invasive, is provided, and newly developed devices for the measurement of rotatory knee laxity are considered. Recent advances with respect to the pivot shift test are explained and evidence offered to support a standardized pivot shift test and non-invasive quantification of the pivot shift. Specific surgical techniques for rotatory laxity are described, with presentation of the experience from several world-renowned centers. In addition, functional rehabilitation and "return to play" are discussed. In keeping with the emphasis on an individualized approach, the book highlights individualization of surgical reconstruction techniques in accordance with the specific injury pattern and grade of rotatory knee laxity as well as the use of individualized rehabilitation techniques. Numerous high-quality images illustrate key points and clear take-home messages are provided.
Keywords: Medicine.; Orthopedics.; elektronické knihy; electronic books